Language, Identity, and Fandom: A Sociolinguistic Study of Manchester United Supporters - Trisnian Ifianti; Enis Fitriani (Universitas Insan Budi Utomo, 2026)
Language is essential in shaping and articulating social identity within fan communities. Football fans, notably, utilise unique linguistic methods to express allegiance, unity, and affiliation with a particular community. This research examines the manner in which Manchester United fans formulate their linguistic identity using language employed in digital communications. Utilising a qualitative sociolinguistic framework, the research examines remarks, hashtags, slogans, nicknames, and football-related terminology gathered from social media channels like X (formerly Twitter), Reddit, and Facebook. The examination is directed by Bucholtz and Hall's (2005) model of identity formation, Tajfel and Turner's (1979) Social Identity Theory, and Labov's sociolinguistic viewpoint on linguistic variety. The results are anticipated to reveal that Manchester United fans forge a communal linguistic identity via club-specific terminology, inclusive pronouns, evaluative language, humour, competitive dialogue, and symbolic representations. These linguistic tools enhance communal unity while differentiating adherents from opposing fan factions. The research enhances sociolinguistic inquiry into language, identity, and digital fandom by demonstrating how football fans utilise language as a symbolic tool for shaping collective identity.